LEGAL UNIFICATION POLICY ON THE COMPARISON OF THE TRADITIONAL LEGAL SYSTEMS OF BALI AND LOMBOK - Md. Shodiq; Arya Bagiastra; Giyarto (Scholar Express Journals, 2024)
One manifestation of the nation's socio-cultural values is the application of customary law rules as living laws in society. Customary law, as the living law, grows and develops in accordance with the development of the community's sense of justice. the reality of the application of the customary law system in Indonesia, namely between the customary law system in Bali and that in force in Lombok, West Nusa Tenggara. We chose these two study loci randomly, but are still based on discourse regarding the customary legal system on the one hand, and its relevance to legal development in Indonesia on the other hand. Problem formulation What is the urgency of the customary law system, in this case including Balinese and Lombok customary law, towards legal development in Indonesia? How is the implementation of the customary law system in Bali and Lombok for legal development efforts in Indonesia viewed from the context of legal pluralism? Normative legal research methodology with a statutory approach, a historical approach, a comparative approach and a conceptual approach. Conclusions and recommendations for a comprehensive search regarding the comparison of customary legal systems in Indonesia so that it can be more comprehensive. carried out intensively, considering that the urgency of law for the way of life of the people of this nation is still very much needed on the one hand. Meanwhile, on the other hand, it becomes a "laboratory" for state legal officials or in this case those representing the government to always consider aspects of the benefits of the law itself for society in the midst of efforts to implement legal unification or legal pluralism policies.
Keywords: Customary law system; Lombok and Bali; legal pluralism